Panel data econometrics : methods-of-moments and limited dependent variables - Lee, Myoung-jae. (San Diego : Academic Press, 2002)
Describes developments in panel-data econometrics, focusing on implemention and computational feasibility of estimation methods. This book compares parametric and semiparametric approaches, provides estimators for response models, presents methods in panel data analysis, and, describes ideas behind generalized method of moments (GMM) estimation.
Includes bibliographical references (p. 184-192) and index.
oif 05/05/15
Loan
Keywords: Panel analysis; Econometric models